PERSEPSI MAHASISWA AKUNTANSI, PRAKTISI NON SYARIAH, DAN PRAKTISI SYARIAH TERHADAP PRAKTISI SYARIAH - Irdianti, Devi (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2014)
The purpose of this study are as follows: (1) To determine differences in perception between accounting students andpractitioners of shariah about shariah practitioners. (2) To determine differences in the perception of non-syariahpractitioners and practitioners of shariah about shariah practitioners. (3) To determine differences in perceptionbetween accounting students and practitioners of non- shariah practitioners about shariah practitioners . Sampling method used in this study is purposive sample selection. The sample in this study was 60 accountingstudents who have studied syariah accounting the in Islamic University "45" Bekasi, 32 non-syariah practitionerswho worked at Bank BRI Jelambar, 18 shariah practitioners working in Bank Mandiri Syariah Kalimas. This studyused descriptive method and Independent Sample T-Test using SPSS program. The results show that: (1) There werestatistically significant differences between accounting students and practitioners sharia about sharia practitioners.(2) There is no significant difference between the practitioners of non-syariah and shariah practitioners againstpractitioners of sharia. (3) There were statistically significant differences between accounting students who hadstudied accounting Shariah and non-Shariah practitioners against practitioners of sharia